Spatially Pressure‐Mapped Thermochromic Interactive Sensor. Issue 13 (24th January 2017) - Kim, Gwangmook; Cho, Sungjun; Chang, Kiseok; Kim, Wook Sung; Kang, Hansaem; Ryu, Sung‐Pil; Myoung, Jaemin; Park, Jinwoo; Park, Cheolmin; Shim, Wooyoung
Abstract : A thermochromic‐based interactive sensor that can generate local color switching and pressure mapping is developed using a 2D array of resistive pressure sensor switch. This thermochromic‐based interactive sensor will enable the visualization of localized information in arbitrary shapes with dynamic responses in the context of serial/parallel pressure mapping and quantifying capability without optoelectronic arrays.